Analysis of Directive Speech in the Novel The Village Boy by Damien Dimatra - A. Saibi, Elvina (KnE Social Sciences, 2022)
This study describes the types of directive speech in the novel The Village Boy. A directive speech act is an utterance expressed through the attitude of the speaker so that the speech partner receives the implied message and acts according to what the speaker intended. Descriptive methods were used in this study. The listening and note-taking method was used to collect data, which were analyzed using the matching method and the determining element sorting technique (DEST). Based on the results, in the novel The Village Boy, seven types of directive speech acts were found, namely: 1. directive speech acts ordered marked by markers (try, subtle illocutionary signal power, subtle illocutionary signal power with interrogative sentences and strong cues); 2. pleading (please, beg, hopefully, and the illocutionary power of subtle cues and subtle illocutionary cues); 3. demanding (should and the illocutionary power of soft cues and strong illocutionary cues); 4. suggest (should ask, better, the illocutionary power of subtle cues and strong illocutionary cues); 5. ask (ordinary questions and rhetorical questions); 6. forbid (don’t, the illocutionary power of soft cues and strong illocutionary cues); and 7. allow (please, let, bless, say, goodbye, illocutionary power of soft cues and strong illocutionary cues). Keywords: speech act, directive, novel